Influence of cytosolic conditions on the reaction equilibrium and the reaction enthalpy of the enolase reaction accessed by calorimetry and van ‘t HOFF - Vogel, Kristina; Greinert, Thorsten; Harms, Hauke; Sadowski, Gabriele; Held, Christoph; Maskow, Thomas (Biochimica et biophysica acta. General subjects, 2020)
Thermodynamic methods are finding more and more applications in systems biology, which attempts to understand cell functions mechanistically. Unfortunately, the state variables used (reaction enthalpy and Gibbs energy) do not take sufficient account of the conditions inside of cells, especially the crowding with macromolecules. For this reason, the influence of crowding agents and various other parameters such as salt concentrations, pH and temperature on equilibrium position and reaction enthalpy of the glycolytic example reaction 9 (2-Phospoglycerate - > Phosphoenolpyruvate + H2O) was investigated. The conditions were chosen to be as close as possible to the cytosolic conditions. Poly(ethylene glycol) MW = 20,000 g mol−1 (PEG 20,000) was used to analyze the influence of crowding with macromolecules. The equation of state electrolyte Perturbed-Chain Statistical Associating Fluid Theory (ePC-SAFT) was applied to consider the influence of crowding agents on the reaction equilibria. For the reaction enthalpies and for the equilibria, it was found that the influence of salts and temperature is not pronounced while that of pH and PEG 20,000 concentration is considerable. Furthermore, it could be shown that under identical measurement conditions there are no differences between the van ‘t Hoff and the calorimetrically determined reaction enthalpy. The results show how important it is to consider the special cytosolic conditions when applying thermodynamic data in systems biology. •The standard reaction enthalpy of 2PG- > PEP + H2O is 25.3 ± 1.1 kJ mol−1.•Calorimetric and van ‘t Hoff enthalpy are equal under identical conditions.•The reaction enthalpies depend to a large extent on the cytosolic conditions.•The greatest influence is the crowding by macromolecules and the pH value.•ePC-SAFT allows the prediction of cytosolic conditions.